Preparation and characterizations of three-dimensional porous collagen/graphene oxide/hydroxyapatite nanocomposite scaffolds for bone tissue engineering - Zimba, Bhahat Lawlley; Hao, Jiang; Li, Chen; Yaomin, Li; Xunzhi, Yu; Chang, Chen; Jiangling, Wan; Wu, Qingzhi (Open Science Journal, 2019)
Studies have reported that the incorporation of graphene oxide (GO) and hydroxyapatite (HA) into biocompatible polymers (such as collagen (Col), chitosan, alginate, etc) results in enhanced structural and mechanical properties respectively. The objective of this study was to prepare and characterize three-dimensional (3D) porous Col/GO/HA nanocomposite scaffolds and to investigate cytocompatibility and osteogenic differentiation potential of rat bone marrow mesenchymal stem cells (rBMSCs) on the as-prepared scaffolds. The SEM images revealed that the scaffolds were porous with the pore diameter inversely proportional to the concentration of HA. XRD results were able to depict the characteristic peaks for HA which shows that HA was incorporated into the scaffolds. The rBMSCs which were cultured on the scaffolds were able to attach and proliferate during the 21 days of the experiment which indicates that the as-prepared scaffolds are cytocompatible. The Alizarin red staining demonstrated the presence of calcium deposits as there were orange-red stains on the samples after culturing the cells using the osteogenic differentiation medium. These results demonstrate the promising potential of the 3D porous Col/GO/HA nanocomposite scaffolds for applications in bone tissue engineering.